Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1139/z00-185
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of bot flies (Cuterebra fontinella) on white-footed mice (Peromyscus leucopus) near forest edges

Abstract: Several studies have suggested that forest edge is preferred habitat for white-footed mice (Peromyscus leucopus). Because previous research has shown that parasitism by bot flies (Cuterebra fontinella) is higher in open areas than in woodlands, lower rates of infestation at woodland edges could partly explain the greater preference for woodland edges by the mice. We recorded the prevalence and load of bot fly larvae in mice trapped along edge-to-interior gradients in four forested areas in east-central Illinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…et al 1998, Sisk & Battin 2002. Parasitism is also higher at edges for some amphibians (Schlaepfer & Gavin 2001) and mammals (Wolf & Batzli 2001). There is less evidence for consistent effects of predation and parasitism on invertebrates.…”
Section: Species Interactionsmentioning
confidence: 98%
“…et al 1998, Sisk & Battin 2002. Parasitism is also higher at edges for some amphibians (Schlaepfer & Gavin 2001) and mammals (Wolf & Batzli 2001). There is less evidence for consistent effects of predation and parasitism on invertebrates.…”
Section: Species Interactionsmentioning
confidence: 98%
“…Several studies have investigated the behavioural effects of botfly parasitism and have determined that botflies generally have little effect on Peromyscus compared to atypical hosts, such as non-native rodents, lagomorphs, and Carnivora, which experience physiological and behavioural changes resulting in decreased activity, food intake, and reproductive success (Slansky 2007). Nonetheless, individuals can be adversely affected by botfly parasitism, and a smaller dispersal distance from the natal nest was noted in the offspring of parasitized individuals (Wolf and Batzli 2001;Jaffe et al 2005). I offer this account of a female deer mouse eating a parasitizing botfly as the first account of a mechanism by which deer mice may mitigate the effects of botfly parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat complexity (i.e., tree basal area, sapling basal area and CWD volume) was not a signiWcant predictor of infection patterns when vole abundance was taken into account. Although other studies found that infection patterns of bot Xies in small mammals appeared to be related to habitat attributes (Hensley 1976;Wolf and Batzli 2001;Cockle and Richardson 2003), we identiWed host abundance in August as the main factor driving both the probability of infection and the abundance of bot Xies.…”
Section: Infection Patterns Of Bot Xies In Red-backed Volesmentioning
confidence: 94%